(untitled) (Progressive Agriculture, 2018)
The present study was conducted to reveal the present scenario, problems and the prospect of fish farming of Gazipur Sadar upazila Bangladesh. The primary data were collected through field survey, questionnaire interview and focus group discussion from the fish farmers of several villages and urban areas of the upazila. Secondary data were collected from the Department of Fisheries and aquaculture extension section. Gazipur Sadar upazila has 14462.42 ha potential fisheries resources of which floodplains, seasonal water bodies, and ponds comprise 71.01%, 13.04%, and 8.57%, respectively. The total fish production of the upazila in 2016-17 was 14492.7 MT, 27% of the Gazipur district. The highest fish production of 5436 MT and 4.39 MT/ha/year came from the pond sector. Among different pond culture systems, the semi-intensive system had the highest fish production output (2826 MT). Exotic carps were the highest produced fish in the ponds. However, in spite of comprising a huge proportion of seasonal floodplains the fish production from this sector was only 0.42 MT/ha/year in 2016-2017. This indicates the poor utilization of inland open water resources for fish production in the study area. The major areas were identified to improve the existing pond fish farming situation were access to low-interest loan, quality seed, supply of advanced technologies, need-based training, and marketing facilities. Along with improving the pond fish farming, community-based fisheries management and some aquaculture initiatives on private own seasonal floodplains should be taken on a priority basis to improve open water management and to flourish inland fish production in the study area. Progressive Agriculture 29 (1): 53-63, 2018